Thinking places: towards application of place-based GIS in urban morphology - Slivinskaya, Liudmila (Technische Universität Dortmund, 2022)
This article sketches out a tentative direction towards potentials that might be opened by the formalization of place through place-based GIS for the study of urban form. In particular, models of place based on function and affordances are touched upon to explore their relevance within the domain of urban morphology under contemporary urban conditions. Established morphological relations and hierarchies of elements of urban form become more and more fragmented as new complex hybrid typologies emerge and proliferate. Such new types of spaces, being highly flexible, multi-layered, ever increasing in complexity, entangling built forms and open spaces, merging inside and outside, featuring stacks of green spaces in sophisticated vertical programming, call for an equally complex and multidimensional vision of urban form, its generative and operational principles. There is thus a need to search for new ways and approaches to take the conceptualization of urban form further, beyond its mere geometrical properties. Functional imperatives inter alia drive formation and transformation of urban form. Could then a place, understood through its functions or affordances, offer deeper insights into formation, emergence, and operation of urban form today? Could such formalization, embedded into GIS, allow for richer data flows to be analysed, opening up new experiential and operational facets of urban form? Could it lead towards better integration of a human-centred perspective allowing us to see 'lived' or 'experienced' urban form not only through phenomenological, subjective, individual accounts or narratives, but also as it is embedded in abstract blank space? Such are the questions touched upon by the article.
Keywords: space; place; platial; place-based GIS; 710